In subordination professional women, 1870 - 1970 - Kinnear, Mary (McGill-Queen's Univ. Press, 1995)
"From 1870 to 1970 between ten and twenty per cent of women in paid work held jobs described by the Canadian census as "professional." In this important study Mary Kinnear examines the experience of the first generations of professional women in Canada." "Kinnear presents case studies of women in five professions - university teachers, physicians, lawyers, nurses, and schoolteachers - in Manitoba. She shows that all five professions had three characteristics in common: unequal pay, lack of control by women, and the belief that marriage and the professions were not compatible. Most women, whether in male- or female-dominated professions, were forced to accept subordinate positions, to which they responded with acquiescence, indifference, resentment, or resistance. Kinnear considers the reasons for and the cost of these various strategies." "In addition to quantitative data from census and other records, Kinnear has collected the testimony of more than two hundred professional women. A significant contribution to the growing literature on women and the professions, In Subordination helps explain why professional women continue to fight for equality today."--BOOK JACKET.